Bingo of genetic code: A low cost playful game to facilitate the learning of the theme in the discipline of Genetics (Research, Society and Development, 2021)
Currently, the teacher is faced with several alternative educational methodologies that make the traditional expository method increasingly improved. Added to this, education has gone through delicate moments at the expense of the new Coronavirus pandemic (SARS-CoV-2). The use of educational games has been highly appreciated for facilitating and motivating student learning. In higher education, the genetic code theme is generally seen as complex and difficult to assimilate due to the vast amount of terms and concepts that need to be assimilated. The objective of this work is to propose a game that facilitates the understanding of the genetic code theme in the genetics discipline. In addition, the game allows you to approach topics of Biochemistry, regarding the characteristics of the structural constitution of amino acids, and other concepts such as essential, non-essential or conditionally essential amino acids. We believe that the use of this activity can captivate students and promote improvement in the teaching and learning process on the subject.